Standardization of Immunocytochemical method for the diagnosis of Dengue Viral Infection in Aedes aegypti Linn Mosquitoes (Diptera Culicidane) - Umniyati, Sitti Rahmah (Universitas Gadjah Mada, 2009)
methods for virus detection in the mosquito, such as the direct fluorescent-antibody test on head squashes. However, it has the disadvantages of being labor-intensive and requiring fluorescent microscope as well as cryofreezer. Newer methods involving enzyme conjugates such as peroxidase in conjunction with either polyclonal or monoclonal antibodies are greatly improved. With new methods of immunocytochemistry, it is now possible to detect dengue viral antigen in a variety of tissues. Objective: This study was aimed to standardize an immunocytochemical streptavidin-biotin-peroxidasecomplex assay for diagnosis of dengue infection in Aedes aegypti using monoclonal antibody DSSC7. Methods: The infected mosquitoes were held in small cylindrical cages covered with mosquito netting, and incubated at 27:t 1Â°C ami at relative humidity of 88:t 6 %. The specificity of the immunocytochemical procedure was validated by negative and positive controls showing that the antibody was bound to an appropriate structure. The sensitivity and specificity were also evaluated based on Herrmanns Formula. The presence of dengue antigen on head squash preparation was detected based on ISBPC assay using monoclonal antibody against dengue. The validity and reliability of the measurement were evaluated based on kappa values, according to Landis and Koch. Result: Positive result was detected as discrete brownish granular deposits throughout most visual fields of brain tissue. Dengue viral antigen was immunolocalized to the cytoplasm of brain cells. The immunocytochemical test under light microscope at magnification of 400x was 86.67% sensitive, 96.00% specific, and the kappa value is 0.64. Meanwhile the kappa value between two observers was 0.92, with sensitivity and specificity of 96% and 97% respectively at magnification of 1000x. Conclusion: The monoclonal antibody DSSC7 was sensitive, specific, valid, and reliable as primary antibody to detect dengue viral infection in Ae. aegypti head squash preparation based on immunocytochemical streptavidin-biotin-peroxidase-complex assay under light microscope. Key words: antigen - denguevirus - Aedes aegypti - immunocytochemistry - monoclonal antibody DSSC7